Drought responses on growth, proline content and root anatomy of Acacia auriculiformis cunn., Tectona grandis l., Alstonia spectabilis br., and Cedrela odorata l. - Rina Laksmi Hendrati; Diah Rachmawati; Asri Cahyaning Pamuji (Foresty Faculty of Hasanuddin University, 2016)
Global warming causes extreme weather and temperature leading to drought. Identification of drought adaptive species is essential. This research is aimed to examine growth, proline content and root anatomy of Acacia auriculifomis, Tectona grandis, Alstonia spectabilis, and Cedrela odorata and to compare the most adaptive species under drought condition. Controlled dry treatments applied were 10, 20, 30, and 40 days unwatered, and compared with control plants, each with 3 replications. Characteristics measured were height, diameter, leaf number and area, root proline content and root tracheal diameter. Data and samples were collected every 10 days. Growth and physiological data were analyzed by using T-Test, while anatomical data were analyzed by using ANOVA and DUNCAN test. Results showed that drought on A. auriculiformis, T. grandis, A. spectabilis, and C. odorata has decreased plant height, stem diameter and number of leaves but increasing proline content, and diameter of tracheas belonging to the roots. This study indicates that the most likely tolerant and adaptive species to drought are those that have the most variation of mechanisms to respond in which these characters would likely to appear at higher level of stress condition.